On Cesàro Sequence Space defined by an Orlicz Function - Bala, Indu (Communications in Mathematics and Applications, 2022)
In this paper we provide a suitable generalization of the sequence space ${\it ces}_{M}$ of Orlicz [6] by using a sequence of strictly positive real numbers and study various topological properties and inclusion relations which generalize several known results of Orlicz [6], Shiue [9], Sanhan and Suantai [8], and Leibowitz [3].